The Kinematic Effects of the Defects in Liquid Crystal Dynamics (Communications in Computational Physics, 2018)
Here we investigate the kinematic transports of the defects in the nematicliquid crystal system by numerical experiments. The model is a shear flow case of theviscoelastic continuum model simplified from the Ericksen-Leslie system. The numericalexperiments are carried out by using a difference method. Based on these numericalexperiments we find some interesting and important relationships between the kinematictransports and the characteristics of the flow. We present the development andinteraction of the defects. These results are partly consistent with the observation fromthe experiments. Thus this scheme illustrates, to some extent, the kinematic effects ofthe defects.